Family Life in the Time of COVID International perspectives - Twamley, Katherine; Iqbal, Humera; Faircloth, Charlotte (UCL Press, 2023)
COVID-19 turned the world as we knew it upside down, impacting families around the world in profound ways. Seeking to understand this global experience, Family Life in the Time of COVID brings together case studies from 10 countries that explore how local responses to the pandemic shaped, and were shaped by, understandings and practices of family life. Carried out by an international team during the first year of the pandemic, these in-depth, longitudinal, qualitative investigations examined the impact of the pandemic on families and relationships across diverse contexts and cultures. They looked at how families made sense of complex lockdown laws, how they coped with collective worry about the unknown, managed their finances, fed themselves, and got to grips with online work and schooling to understand better how life had transformed (or not). In short, the research revealed their everyday joys and struggles in times of great uncertainty. Each case study follows the same methodology revealing experiences in Argentina, Chile, Pakistan, Russia, Singapore, South Africa, Sweden, Taiwan, the United Kingdom and the USA. They show how local government responses were understood and responded to by families, and how different cultures and life circumstances impacted everyday life during the pandemic. Ultimately the analysis demonstrates how experiences of global social upheaval are shaped by international and local policies, as well as the sociocultural ideas and practices of diverse families.